Mistakes of Parents in Educating Children According to Edy Wiyono in the Perspective of Islamic Education - Zulkifli Agus (LPPM Institut Studi Islam Sunan Doe, 2024)
The purpose of this study is to find out the mistakes of parents in educating children according to Edy Wiyono in the perspective of Islamic education. This research is a literature review research in which the data is taken from various reliable sources, both-articles, books or other research sources. The results of this study are that parents are the primary and first educators in terms of instilling faith in their children. Called the primary educator, because of its enormous influence. Called the first educators, because they are the first to educate their children. Schools, Islamic boarding schools and ustadz who are invited to the house are educational institutions and people who only help parents. Delivering one hundred percent faith education for children to schools, Islamic boarding schools, and/or ustadz who are invited to the house is an inappropriate action. Because the schools, Islamic boarding schools and ustadz who were invited would not be able to carry out this faith education without the help of parental guidance.